Production of ferulic acid via feruloyl polysaccharide hydrolysis of banana stem waste using soil mixed culture - Nurul Shareena Aqmar, Mohd Sharif (2021)
The source of lignocellulose is abundantly available through agricultural wastes and often discarded in the landfill. These wastes are not just potentially produce organic compound, but also could be the source to generate crude enzyme. This study proposed the used of soil mixed culture (SMC) for feruloyl-polysaccharide hydrolysis from banana stem waste (BSW) to produce ferulic acid (FA). Method used was comprised of multivariate analysis through full factorial design (FFD) and central composite design (CCD) to investigate and optimize the effect and interaction of five factors; fermentation temperature (A; 26 – 40 oC), agitation (B; 0 – 150 rpm), water-to-BSW ratio (C; 1 – 2 v/v), substrate-to- inoculums ratio (D; 1 – 2 v/v), and incubation time (E; 24 – 120 h). Then, a study of kinetic modelling was performed based on Michaelis-Menten model to observe the process behaviour. Lastly, five most dominant bacteria from SMC were identified and later be compared on their ability to produce FA. Series of batch fermentation were conducted at triplicate according to the parameter values of experimental runs generated by the design. A 25 linear model of FFD was well fitted at R2=0.8019 with factors contribution in the order of E > C > A > D > B. Factor E had 27.37% contribution with an optimum range at 12 – 36 h, indicating the significance of cell growth activities, while interaction of DE was highest revealing the importance of sufficient time for substrate utilization to get high FA yield. Parameter E and C were selected as the variables for a 52 CCD based on response surface methodology (RSM) at values range of 12 to 36 h and 0.5:1 to 1.5:1 v/v, respectively. The R2 value for the quadratic model was fitted at 0.8068. Interaction between these factors revealed that effect of time was greater than ratio of water-to-BSW, as expected. The maximum FA produced was 1.1657 mg FA/g BSW at the optimum condition of 27 h incubation time and 1.1:1 water to BSW ratio. With this value, experiments were conducted at a prolonged of 60 h incubation time, where FA yield was observed at every 6 h time interval to develop the study of Michaelis-Menten kinetic model. The kinetic constant, Ks (reaction rate coefficient), Km (Michaelis-Menten constant) and Vmax (maximum forward velocity) from first-order reaction equation and Michaelis –Menten model were determined based on the sum squared error between experimental data and theoretical data by using Excel Solver. The initial concentration of biomass [So] and FA yield [Po] were 7.4150 g biomass/L and 1.3710 mg FA/g BSW, respectively. The values of calculated kinetic parameters were: Ks = 0.0053 h-1; Vmax = 4.1200x10-5 μmol/min; Km = 0.0500 mmol/L. The R2 values obtained from squared error calculation were satisfactorily more than 0.800 which verified the stability of the system. Then, five most stand out pure strains were identified and their performance on FA yield were observed as follows: Brevundimonas nasdae s. W1-2B = 0.4535 mg FA/g BSW; Pseudomonas monteilii s. CIP 104883 (B) = 0.7919 mg FA/g BSW; Pseudomonas monteilii s. CIP 104883 (C) = 0.8302 mg FA/g BSW; Lysinibacillus boronitolerans s. 10a = 0.8249 mg FA/g BSW; and Bacillus anthracis s. Ames = 0.8383 mg FA/g BSW. Meanwhile, using SMC, highest FA yield was 1.4597 mg FA/g BSW. It can be concluded that, BSW was proven to be useful and highly feasible for producing FA, which is useful in pharmaceutical industry. Furthermore, using SMC as the source of inoculum to generate enzymes for hydrolysis of BSW was potentially abled to produce FA as efficiently.